Acute eosinophilic pneumonia following aromatherapy with essential oil. (2022) - Kodama, Tatsuya; Watanabe, Takanori; Mataki, Norikazu; Kanoh, Soichiro; Kichikawa, Yoshiko
Abstract: Essential oils are liquid extracts of various plants with potential health benefits and are often used in aromatherapy. Contact allergy, including skin irritation, is a well-known side effects of these extracts. A Japanese woman visited our emergency department complaining of dyspnea, cough, and fever. Two weeks earlier, she had started aromatherapy using a humidifier and essential oil. Based on clinical and imaging findings, and the results of bronchoalveolar lavage, we diagnosed acute eosinophilic pneumonia due to inhalation of essential oil. Her symptoms resolved after steroid therapy. This case makes the clinicians aware the possibility of acute eosinophilic pneumonia induced by aromatherapy using essential oil.